Imitation of Christ - "Kempis, Thomas A" (New York, 1977)
Only the Bible has been more influential as a source of Christian devotional reading than The Imitation of Christ. This meditation on the spiritual life has inspired readers from Thomas More and St. Ignatius Loyola to Thomas Merton and Pope John Paul I. Written by the Augustinian monk Thomas à Kempis between 1420 and 1427, it contains clear instructions for renouncing wordly vanities and locating eternal truths. No book has more explicitly and movingly described the Christian ideal
Keywords: Jesus Christ